An agroecological turn in intermediating sustainability transitions with continuous living cover - Conway, Tara Maireid (Frontiers in Sustainable Food Systems, 2023)
Continuous living cover's (CLC) perennial and winter annual crop varieties present a novel opportunity to increase the diversity and resiliency of agroecological systems in the Mid-Continent of North America. However, transforming the predominant agri-food regime remains a complex and daunting undertaking. In the face of such complexity, a recent body of literature highlights the particular importance of intermediaries in facilitating sustainability transition processes, which CLC agriculture's proponents can draw upon. Intermediaries can be defined as actors or organizations that positively influence sustainability transition processes by linking diverse entities, networks, institutions, activities and their related skills, knowledges, and resources. Simultaneously, agroecology, in the more political understanding of the term, can serve as an evaluative framework for agri-food transition processes to augment our understanding of intermediaries in sustainability transitions. This mini-review presents an overview of the emerging sustainability transition intermediary literature, an introduction to CLC agriculture's transition intermediaries, and the research gaps highlighted from an agroecological perspective. Integrating an agroecological lens attentive to the science, practice, and politics of intermediating agricultural transitions, this review proposes an adapted framework to understand and assess CLC agriculture's intermediaries. Thus, CLC agriculture presents a unique opportunity to iteratively draw upon and advance the sustainability transition intermediary literature.